2015
DOI: 10.1111/grow.12103
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants Doing Business in a Mid‐sized Canadian City: Challenges, Opportunities, and Local Strategies in Kelowna, British Columbia

Abstract: Lacking a tradition of settling immigrants and the appropriate infrastructure to integrate them, small‐ and medium‐sized cities often face the challenge of attracting and retaining immigrants. Using a mixed methods approach, this study compares the experiences of immigrant and non‐immigrant entrepreneurs in a mid‐sized Canadian city, Kelowna, British Columbia. A survey reveals different experiences between these two groups, with immigrants facing more challenges. In the absence of institutionally complete comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…Family trust creates an environment which permits responsive conversations for exchanging points of view and information that is useful for crafting an entrepreneurial idea. Previous research indicates that trust provides a foundation for entrepreneurial development (Deakins, Smallbone, Whittam & Wyper, 2007) and that immigrants appreciate the trust of family members and also confirm the central importance of family members in their businesses (Lo & Teixeira, 2015). In our cases, families of immigrant entrepreneurs in the host and home countries were prepared and available to discuss entrepreneurial ideas as and when needed.…”
Section: Please Insert Table 5 Heresupporting
confidence: 71%
See 1 more Smart Citation
“…Family trust creates an environment which permits responsive conversations for exchanging points of view and information that is useful for crafting an entrepreneurial idea. Previous research indicates that trust provides a foundation for entrepreneurial development (Deakins, Smallbone, Whittam & Wyper, 2007) and that immigrants appreciate the trust of family members and also confirm the central importance of family members in their businesses (Lo & Teixeira, 2015). In our cases, families of immigrant entrepreneurs in the host and home countries were prepared and available to discuss entrepreneurial ideas as and when needed.…”
Section: Please Insert Table 5 Heresupporting
confidence: 71%
“…The family was thus a repository of trust to interact with the larger social structure (Aldrich & Waldinger, 1990). The trust generated in the family enabled individuals to make sacrifices of individual interests for the benefit of the group (Portes & Sensenbrenner, 1993;Lo & Teixeira, 2015). However, we know little about how trust influences the process of creating opportunities.…”
Section: Family Social Capital and Opportunity Creationmentioning
confidence: 99%
“…In cities such as New Orleans (Airriess ) and Toronto (Teixiera et al ), scholars have demonstrated that immigrants turn to co‐ethnics in forming ethnic economies. However, in new immigration gateway cities such as Washington, D.C. (Price and Chacko ) or mid‐sized cities such as Kelowna, Canada (Lo and Teixiera ), where strong ethnic economies are missing, immigrants and ethnic minorities cannot rely extensively on their own community resources. The current study differentiates the “ethnic community” by residence and by business.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in their interviews with immigrant entrepreneurs, González‐González and Bretones () noted that those involved in family businesses saw benefits in the flexibility, control, and dedication that family members can provide, and that these businesses serve as a source of pride for the family. It is not simply a matter of convenience that family is involved; immigrants appreciate the trust, interest, and commitment of family members and are more likely than nonimmigrants to affirm the central importance of family members in their business (Lo & Teixeira, ). Thus, an interpretation of the results is that if an entrepreneur's desire is to include family, whether immediate or extended, then a reasonable way to involve these family members would be to create a business based on a shared cultural heritage.…”
Section: Discussionmentioning
confidence: 99%